Perbedaan Status Kesehatan dan Pertumbuhan Bayi pada Ibu Pekerja dan Ibu Bukan Pekerja Kota Jambi - Armina, Armina; Nurfitriani, Nurfitriani; Irlandes, Ciria (Prosiding Seminar Kesehatan Nasional, 2024)
Growth pattern is a description of physiological changes as a result of the maturation process of physical functions that occur normally in healthy children at normal times with the fulfillment of immunization, vitamin A and avoidance of pain. Based on the coverage of toddlers who were weighed in 2020, Jambi City had the lowest rate of 34.88%, the prevalence of short toddlers in Jambi City was 18.62% in 2019, the coverage of vitamin A administration in 2020 aged 6-11 months was 77.87%. The purpose of this study was to determine the Growth and Health Status of Toddlers aged 6-12 months in Working Mothers and Non-Working Mothers in the Working Area of the Ayu Health Center, Jambi City. Data collection for this study was carried out in May 2024 at two posyandu in the working area of the Putri Health Center. The population of this study were babies aged 6-12 months with a population of 20 babies, the sampling technique used total sampling. The analysis of this study was univariate. The results of this study are the baby's weight according to the WHO age curve of the majority of 100% in working mothers, the baby's length according to the WHO age curve of the majority of 87.5% in working mothers, giving vitamin A at 6 months of age the majority in working mothers, namely 87.5%, basic immunization according to age is the same in working mothers and non-working mothers, mixed breastfeeding is given to the majority of babies of non-working mothers and working mothers, a history of respiratory illness in the majority of babies of non-working mothers and working mothers, a history of giving homemade complementary foods in the majority of babies of non-working mothers and giving homemade mix instant complementary foods to babies of working mothers.